SOSIALISASI PENCEGAHAN PERNIKAHAN DINI PADA SISWA SISWI SMA NEGERI 1 LEMBAH MELINTANG, NAGARI SALIDO SAROHA UJUNG GADING, KECAMATAN LEMBAH MELINTANG - Devina Sari Siregar; Muhammad Fadli, Muhammad Surya, Muhammad Muslih, Rahmadani, Siti Makwa Nst, Aida Sari, Mahya Azizah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Early marriage is a phenomenon that is of major concern in health and human rights issues among society globally. Early marriage is usually dominated by women, especially in rural areas. Some parents give permission and let their children marry before the age of 18. Some parents think that marrying their children off at a young age can ease the economic burden on the family. Even though early marriage has a negative impact on both the prospective mother and the prospective child. This service aims to provide education to students at SMA Negeri 1 Lembah Melintang regarding the impact of early marriage and the factors that cause early marriage so that students avoid marriage at an early age and focus on studying. The method for carrying out this activity is by providing information about early marriage, providing direction and motivation. This socialization activity received a positive and quite enthusiastic response from both teachers and students because it was followed by promotion of the STAIN Madina campus and inviting younger students to study at the Pride Campus of Mandailing Natal Regency.